2014
DOI: 10.1007/s11357-014-9735-z
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender effects on submental motor-evoked potentials

Abstract: It is not known whether there are ageand/or gender-related differences in magnitude of motor-evoked potentials (MEPs) of the submental muscles. Knowledge of this is important in investigations of neurophysiological aspects of swallowing. Forty healthy participants (20 males, 20 females; 20 young [21-35 years], 20 old [53-88 years]) were recruited. Surface electromyography (EMG) electrodes were placed at midline underlying the submental muscle group. Age-and genderrelated differences were evaluated in two neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
5
8
0
Order By: Relevance
“…In our study, the pharyngeal MEPs were harder to elicit compared to those of other muscles, such as those controlling the hand. While the amplitudes of MEPs from hand musculature have been reported to be mostly above 200mV [37,38], those from the pharyngeal muscles in our study were only around 35mV, which is consistent with previous studies [8,39,40]. Most of the PMEPs we observed were of a two-peak form, which is in line with N. Freundlieb et al This study pointed out that a two-peak conformation might be due to a higher threshold and a lower number of neurons being stimulated [13] that would thus result in smaller cortical representations, lower amplitudes and two-peak MEP shapes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the pharyngeal MEPs were harder to elicit compared to those of other muscles, such as those controlling the hand. While the amplitudes of MEPs from hand musculature have been reported to be mostly above 200mV [37,38], those from the pharyngeal muscles in our study were only around 35mV, which is consistent with previous studies [8,39,40]. Most of the PMEPs we observed were of a two-peak form, which is in line with N. Freundlieb et al This study pointed out that a two-peak conformation might be due to a higher threshold and a lower number of neurons being stimulated [13] that would thus result in smaller cortical representations, lower amplitudes and two-peak MEP shapes.…”
Section: Discussionsupporting
confidence: 93%
“…Despite our important observations, there were also some limitations in our study. It has been reported that the CoG for arm target is more anterior in elderly adults than in young persons [47] and that different MEP amplitudes are elicited across different age groups [39]. However, for convenience, the volunteers we recruited were all young healthy adults and thus the representations and locations that we report may be different than those of elderly adults and cannot be completely and directly translated to patients of all ages [48].…”
Section: Discussionmentioning
confidence: 91%
“…No significant differences in power were observed for either f EMG or s EMG when stratified by sleep stage, age, sex, and sleep disordered breathing, unlike what was reported for waking state EEG 17. As expected, muscle tone in the submentalis decreased on a continuum and was lowest during REM.…”
Section: Discussionsupporting
confidence: 57%
“…The muscles involved in swallowing consist of a greater number of type II muscle fibers than type I, and NMES is a strong stimulus for motor unit recruitment of type II fibers and evokes a contraction. 42 A study done by Sola et al (2017) 39 confirmed that NMES improved swallowing functions in sub acute stroke dysphagic patients, compared to standard swallow therapy, after 3-week intervention. But, no difference was observed at 3-month follow-up between the groups.…”
Section: Discussionmentioning
confidence: 91%